Research of the place of Ukraine in implementation of the goals of the sustainable development model - Kozyk, Vasyl; Vorobets, Stepan; Musiiovska, Oksana (Technology audit and production reserves, 2018)
The object of research is a system of processes for determining the level of a country's development in the context of a sustainable development model. One of the most problematic places is the mistakenly constructed or incorrectly interpreted composite indicators, which can lead to simplified analytical or political conclusions. A study is conducted on the use of composite indicators as tools for identifying development trends in the countries of the European Union, which makes it possible to determine the advantages and disadvantages of their use. And also to establish common and distinctive features with the indicators specified in the Sustainable Development Strategy of the country until 2030. The hierarchical system of composite indicators is built with their subsequent verification for completeness and dimensionality in accordance with the requirements of the selected theoretical and methodological methods of analysis. An interconnected sequence of steps is identified to determine the integral index for each of the studied countries with a view to rating them on the basis of the system of obtained composite indicators and their weight. Based on the obtained eigenvalues of the centered-normalized main components for each of the studied countries and certain substantive interpretations of the main components, a pair-wise comparative analysis is conducted within the studied set of countries. And also carried out a cluster analysis, which allowsto identify groups of countries that are close in value to the integral index. The ranking of the studied countries is carried out on the basis of the calculation of individual integral development indicators, calculated as the sum of its integral indicators for two subsets – stimulant indicators and disincentive indicators. The study of 33 countries allowsto identify the place of Ukraine in the direction of the implementation of individual goals of its development based on a system of composite indicators. And also to assess the relative remoteness of Ukraine both from states that are close in their socio-economic development, and from highly developed European countries.